Difficulty and complexity in dealing with visual pollution in historical cities: The historical city of Ibb, Yemen as a case study. Issue 1 (November 2020) - Alwah, A A Q; Li, W; Alwah, M A Q; Drmoush, A A K; Shahrah, S; Tran, D T; Xi, L B
Abstract: The historical cities in the third world suffer from many environmental problems; one of them is the spread of visual pollution manifestations. These phenomena increase with low levels of public awareness and low per capita income. Despite the historical and cultural importance of the Old City of Ibb, the manifestations of visual pollution are increasing day after day. This study aimed at identifying the difficulty and complexity of dealing with visual pollutions manifestations in the historical city of Ibb and to provide appropriate solutions that are suitable for the complex and contradictory circumstances. The study relies on an inductive approach to achieve its aims through two methods; the first is a visual survey of the visual pollution phenomenon, based on images and observations. The second method is the analyses of the opinions and impressions of three parties related and interested in the phenomenon, namely residents and visitors of the city, competent authorities' officials, and some specialists in the field of the urban environment. The study presents an analysis of the phenomenon of visual distortion of the historical city of Ibb in terms of its appearances and causes. Furthermore, this study provides appropriate solutions, which are suitable for complex and contradictory circumstances. These solutions focused on the methods to stop the spread of visual distortions, and the ways of addressing the current visual pollutions.